2005
DOI: 10.1109/twc.2005.850313
|View full text |Cite
|
Sign up to set email alerts
|

Bit loading with BER-constraint for multicarrier systems

Abstract: Abstract-We present discrete adaptive bit loading algorithms for multicarrier systems with uniform (nonadaptive) power allocation operating in a frequency selective fading environment. The algorithms try to maximize the overall throughput of the system while guaranteeing that the mean bit error rate (BER) remains below a prescribed threshold. We also study the impact of imperfect subcarrier signal-to-noise ratio information on throughput performance. Results show that the proposed algorithms have approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
142
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(143 citation statements)
references
References 10 publications
(30 reference statements)
1
142
0
Order By: Relevance
“…BER is obtained from SER using the approximation [3]. Using this approximation, the optimization problem can be given as…”
Section: Proposed Ofdm Allocationmentioning
confidence: 99%
See 2 more Smart Citations
“…BER is obtained from SER using the approximation [3]. Using this approximation, the optimization problem can be given as…”
Section: Proposed Ofdm Allocationmentioning
confidence: 99%
“…Classically, to achieve a target error rate, SER is fixed on each subcarrier which is equal to the global SER of an OFDM symbol, since all the constellation sizes of QAM have the same value of the SNR gap at the same SER, as it is clear from (2). In this approach, an approximate relation between SER and bit error rate (BER) is used [2] to achieve the target BER of the system, which results in the violation of the target BER in some cases as discussed in [3]. One solution is to fix the BER rather than SER on each subcarrier as proposed in [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be realized by minimizing the Lagrangian (14) where is the transmit-power on the th subcarrier, and the Lagrangian multiplier for the constraint . It can be shown that is a convex and increasing function of .…”
Section: Margin-adaptive Bpl For Sd Communicationmentioning
confidence: 99%
“…The rate-adaptive approach is to maximize the number of bits per block subject to the fixed transmit-power and the target link performance. This approach has also received considerable applications in the OFDM systems (e.g., [14]). …”
mentioning
confidence: 99%